2018
DOI: 10.31557/apjcp.2018.19.11.3077
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality of Moroccan Survivors of Cervical Cancer: A Prospective Data

Abstract: Introduction:This is a prospective study aiming to describe how cervical cancer and its treatment can affect the sexuality of a specific population of Moroccan women survivors of this disease.Materiels and Methods:It is a comparison of clinical features and Female Sexual Function Index (FSFI) of 3 balanced groups of women, made up of 100 survivors of cervical cancer, 100 survivors of non-gynecological cancer and a group of 100 healthy women.Results:97% of the patients stopped their full sexual activity at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Prevalence of sexual activity was assessed by asking women if they engaged in sexual activity during and after the cancer treatment. Sexual function was assessed using the Watts Sexual Function Questionnaire (WSFQ) (Abasher, 2009 ), sexuality items of the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ‐BR23) (Jassim & Whitford, 2014 ; Leila et al, 2016 ), the Female Sexual Function Index (FSFI) (Dahbi et al, 2018 ; Sbitti et al, 2011 ) and investigator‐developed instrument (Errihani et al, 2010 ). The WSFQ is a 17‐item self‐report instrument, and each item is measured on a 5‐point Likert scale (1–5) with scores ranging from 17 to 85.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prevalence of sexual activity was assessed by asking women if they engaged in sexual activity during and after the cancer treatment. Sexual function was assessed using the Watts Sexual Function Questionnaire (WSFQ) (Abasher, 2009 ), sexuality items of the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ‐BR23) (Jassim & Whitford, 2014 ; Leila et al, 2016 ), the Female Sexual Function Index (FSFI) (Dahbi et al, 2018 ; Sbitti et al, 2011 ) and investigator‐developed instrument (Errihani et al, 2010 ). The WSFQ is a 17‐item self‐report instrument, and each item is measured on a 5‐point Likert scale (1–5) with scores ranging from 17 to 85.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported on prevalence of sexual activity in Arab cancer survivors (Abasher, 2009 ; Dahbi et al, 2018 ; Errihani et al, 2010 ; Leila et al, 2016 ; Sbitti et al, 2011 ). The reported prevalence of sexual activity ranged from 3% (Dahbi et al, 2018 ) to 84% (Sbitti et al, 2011 ) (pooled estimate 39.2%, 95% CIs 12.6% to 69.8%, I 2 = 98.1%) (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations